FUNGSI POLITIK PUITIKA MAGIS DALAM CERPEN “ULAR DAN AMARAH” KARYA A.S. LAKSANA DALAM MENGARTIKULASIKAN PANDANGAN TERHADAP KEKERASAN MEI 1998 - Windayanto, Riqko Nur Ardi (University of Brawijaya, 2024)
This research aims to reveal the political function of magical poetics in the short story “Ular dan Amarah” by A.S. Laksana with the theory of magical realism, political function, and articulation. Methodologically, this research consists of poetic data and political data, which are collected, respectively, from short story texts and historical-political-social humanities texts. Both two is analyzed using coherent interpretation and relational analysis between literary work and politics. The are two main findings in this research. First, this short story fulfills the five elements of magical realism so it is a literary work in the magical realism genre. These elements constitute poetics which itself contains a political function. Based on reading the content, parsing discursive words, and the researcher’s knowledge, this short story refers to incidents of violence against ethnic Chinese in May 1998. Second, by making use of the magical, this short story articulates the view that China as a victim is a marginal group that has no power so it must be emphasized and strengthened. This is an effort not to forget this incident and continue to demand state responsibility. The author also criticized this magical thing that violence should not be responded to with violence as done by the character Seto in the short story. On the other hand, non-violent resistance is the “wise” path that must be taken considering that this short story appeared in 2017, dozens of years after the violent incident occurred, resulting in “retention”, which made the violent response change to “wise”.